Comparative study on acoustical performance and occupants' satisfaction between green office buildings and conventional office buildings in Malaysia - Che Din, Nazli; Abd Jalil, Nurul Amira; Manyam Keumala, Nila Inangda (2014)
Green design features and strategies implemented in office buildings are to maximize the us-age of energy efficient whilst reducing building impact onto human health and environment. Optimization of the Indoor Environmental Quality (IEQ) is taking into consideration for re-ducing building impact on human. However, through some amount of experiments based on rating tools for acoustical performances in green office buildings, the authors have come to the question about the effectiveness of green buildings' design strategies onto acoustical com-fort in comparison to the conventional buildings. Thus, the objective of this study is to inves-tigate the level of acoustic performance and occupants' satisfaction on their acoustic environment in green office buildings and in conventional office buildings in Malaysia. Two green office buildings and two conventional office buildings were chosen for the study. To investigate the acoustical performance, series of physical measurement were done to measure the relevant acoustical parameters. Occupants' satisfaction was studied through questionnaire surveys. Initial findings show that the acoustical performance in green office buildings is within the acceptable criteria range. However, in comparison to conventional buildings, it is considered unsatisfactory.